Biomarker Assessment of Homologous Recombination Deficiency in Epithelial Ovarian Cancer: Association With Progression-Free Survival After Surgery - Yi, Huan; Li, Linhong; Huang, Jimiao; Ma, Zhiming; Li, Hongping; Chen, Jian; Zheng, Xiangqin; Chen, Jingjing; He, Haixin; Song, Jianrong (Frontiers in Molecular Biosciences, 2022)
Identifying BRCA mutations and homologous recombination deficiency (HRD) is the key to selecting patients for PARPi therapy. At present, a large amount of research focuses on the application of HRD detection in ovarian cancer. However, few studies have investigated the association between HRD detection and postoperative survival in patients with EOC. This study included 38 consecutive patients with EOC who underwent cytoreduction surgery. Owing to tissue availability, only 29 patients underwent molecular profiling and survival analysis. Overall, 21 (72.4%) tumors were HRD-positive. Mutations in BRCA were observed in 5/29 (17.2%) patients. HRD-positive was observed more frequently in serous ovarian tumors in this cohort. We found no statistically significant association between the HRR genes and HRD scores except for TP53 mutation. We also found a strong positive correlation between HRD scores and chromosomal instability (CIN). In the survival analysis, an HRD score of ≥23 was associated with improved postoperative PFS. In the era of biomarker-driven clinical care, an appropriate HRD score threshold may provide a useful adjunctive prognostic tool and should be evaluated in future studies to predict the benefits of PARPi.